SOPTI Meeting 2020: Abstracts - Zeri, Fabrizio (Scandinavian Journal of Optometry and Visual Science, 2020)
The 25th National Conference of the Italian Optometric Association (SOPTI) was held in Verona on January 19–20, 2020. The theme of the conference was “Innovative technologies in Optometry and Contact Lenses”, was arranged in 3 sessions: optometry, contact lenses, and ophthalmology. Three keynote speakers were invited during the conference: Prof. Rigmor C. Baraas from the University of South-Eastern Norway in Kongsberg, Prof. Silvia Tavazzi from University of Milano Bicocca and Dr. Iwan Zanchetta, clinical practice Rothrist, Switzerland. The abstracts from accepted posters and free papers are presented here.